2010
DOI: 10.1098/rstb.2010.0050
|View full text |Cite
|
Sign up to set email alerts
|

Potassium diffusive coupling in neural networks

Abstract: Conventional neural networks are characterized by many neurons coupled together through synapses. The activity, synchronization, plasticity and excitability of the network are then controlled by its synaptic connectivity. Neurons are surrounded by an extracellular space whereby fluctuations in specific ionic concentration can modulate neuronal excitability. Extracellular concentrations of potassium ([K þ ] o ) can generate neuronal hyperexcitability. Yet, after many years of research, it is still unknown wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 114 publications
(177 reference statements)
1
58
0
Order By: Relevance
“…concentration in the ECS-NA could induce epileptic seizures? A number of results from biological experiments have answered this question (Ohno et al 2015;Cornog et al 1967; Traynelis and Dingledine 1988;Durand and Jensen 2010;Park and Durand 2006). In 2015, Ohno found that down-regulation or dysfunction of K ?…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…concentration in the ECS-NA could induce epileptic seizures? A number of results from biological experiments have answered this question (Ohno et al 2015;Cornog et al 1967; Traynelis and Dingledine 1988;Durand and Jensen 2010;Park and Durand 2006). In 2015, Ohno found that down-regulation or dysfunction of K ?…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the K ? lateral diffusion between two neurons is a significant factor for non-synaptic epileptogenesis in a low-calcium in vitro model (Yaari et al 1986;Park and Durand 2006;Durand and Jensen 2010). Chemical synapses are abundant in the central nervous system.…”
Section: Elevated Bath K 1 Concentration Can Induce Epileptic Seizuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Its overexpression leads to decreased plasma membrane electrical potential by increasing Cl -permeability and thus decreasing the dominance of membrane potential by K + conductance, and leads to altered pHi regulation [47,48]. So, brain P-gp overexpression could contribute to crucial factors detected in several types of epilepsy such as the intracellular acidosis associated with altered Na + /H + exchange [55], enhanced extracellular concentration of potassium [56], and particularly in the increased membrane depolarization [57].…”
Section: Role Of P-glycoprotein In Epileptogenesismentioning
confidence: 99%